ĐÁNH GIÁ ĐỘC TÍNH CẤP VÀ BÁN TRƯỜNG DIỄN CỦA CHẾ PHẨM CHỐNG HÔI CHÂN - Chử, Văn Mến; Nguyễn, Trọng Dân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF THE ACUTE AND SUBCHRONIC TOXICITY OF FOOT ANTI-ODOR PRODUCT In this study, the acute and subchronic toxicity of foot anti-odor product made from laurate salt is evaluated. The results show that the median lethal dose, LD50 of the product hasn’t been found in mice tested with maximum oral dosage . At the dosage of 200 and 400 mg/kg/24h on rabbit, the continuously oral administration for 42 days doesn’t affect the normal weight increment of rabbit and doesn’t change the electrocardiogram; hematological indices such as red blood cell, white blood cell, platelet and hemoglobin content, hepatic indices (AST, ALT activity), renal indices (urea, creatinine levels) are found within normal limits